The Works Metallurgist: an evaluation of a CAL package on phase diagrams - Philip Butcher; Canan Tosunoglu; Eileen Scanlon; Ann Jones (Association for Learning Technology, 1996)
A number of factors have converged today to force the development of more efficient and costeffective educational strategies. These include rapidly changing technology, the increasing number of students in higher education, and resource restrictions imposed on all sectors of education. Educational systems are therefore finding it increasingly difficult to respond to learners' needs, highlighting the need for alternative educational strategies. An increase in the educational use of computers and new information technologies is often one of the suggested alternatives, baised on the premise that computers can support student learning in an individualized way and at the learner's own pace. In this context, evaluation in general and CAL evaluation in particular can contribute to the process of defining and refining educational strategies.